Preparation of Mangosteen Peel Extract Microcapsules by Fluidized Bed Spray-Drying for Tableting: Improving the Solubility and Antioxidant Stability - Sriwidodo Sriwidodo; Reza Pratama; Abd. Kakhar Umar; Anis Yohana Chaerunisa; Afifah Tri Ambarwati; Nasrul Wathoni (MDPI AG, 2022)
Mangosteen fruit has been widely consumed and used as a source of antioxidants, either in the form of fresh fruit or processed products. However, mangosteen peel only becomes industrial waste due to its bitter taste, low content solubility, and poor stability. Therefore, this study aimed to design mangosteen peel extract microcapsules (MPEMs) and tablets to overcome the challenges. The fluidized bed spray-drying method was used to develop MPEM, with hydroxypropyl methylcellulose (HPMC) as the core mixture and polyvinyl alcohol (PVA) as the coating agent. The obtained MPEM was spherical with a hollow surface and had a size of 411.2 µm. The flow rate and compressibility of MPEM increased significantly after granulation. A formula containing 5% w/w polyvinyl pyrrolidone K30 (PVP K30) as a binder had the best tablet characteristics, with a hardness of 87.8 ± 1.398 N, friability of 0.94%, and disintegration time of 25.75 ± 0.676 min. Microencapsulation of mangosteen peel extract maintains the stability of its compound (total phenolic and α-mangosteen) and its antioxidant activity (IC50) during the manufacturing process and a month of storage at IVB zone conditions. According to the findings, the microencapsulation is an effective technique for improving the solubility and antioxidant stability of mangosteen peel extract during manufacture and storage.